The 'healthy side' of anosognosia for hemiplegia: Increased sense of agency for the unimpaired limb or motor compensation?. (15th December 2022) - Cocchini, Gianna; Scandola, Michele; Gobbetto, Valeria; Cioffi, Maria Cristina; Bartolo, Angela; Moore, James; Moro, Valentina
Abstract: Objectives: Anosognosic patients show a lack of awareness for their hemiplegia coupled with a distorted sense of agency for the actions performed by the plegic limbs. Since anosognosia is often associated with right brain damage, this hemisphere seems to play a dominant role in monitoring awareness for motor actions. Therefore, we would expect that anosognosic patients show distorted awareness and sense of agency also for actions performed with the unimpaired limb. Method: To test this hypothesis, we induced illusory actions that could be congruent or incongruent with a preceding verbal command. A group of 16 right brain-damaged patients performed this task and then rated i) their ability to anticipate the actions, ii) their sense of agency and iii) their sense of ownership for each limb. Measures of awareness, neglect and motor impairment were also considered for the patient group. Results: Following incongruent actions with the unimpaired limb, less aware patients showed a relatively mild distortion in all three aspects. In addition, we also found a crucial relationship between motor impairment (for the plegic limb) and sense of agency for both plegic and healthy limbs. Conclusion: Although the distortion linked to both limbs supports the initial hypothesis that the right hemisphere is responsible for monitoring awareness for action for the whole body, our data also suggest that the observed distortion may be linked to a motor compensatory phenomenon, not necessarily related to awareness processes. Highlights: Right-hemisphere networks play a dominant role on ownership, awareness and agency. Motor deficits modulate of sense of agency but not ownership. Motor compensatory processes may conflate with sense of agency. Distortions of agency may be latent for ipsilateral actions also in aware patients. Studies on awareness and agency for actions should consider impact of hemiplegia.